Development of a Web-Based School Library Information System Management Training Model in Labuhanbatu - Simarmata, Petrus Sanjaya; Pangaribuan, Wanapri; Nasrun, Nasrun (Newinera Publisher, 2024)
This research is a response to challenges in school library management, including manual data management and the need for effective human resource management. The research method used is the Research and Development (R&D) method, which consists of several stages such as preliminary studies, development, and product determination. The purpose of this study was to produce an effective training design to improve the quality of web-based library management in Labuhanbatu Regency. The training was aimed at library heads, library staff, and prospective library heads in secondary schools in Labuhanbatu. The needs analysis stage involved interviews and questionnaires to training participants, which indicated the need for increased knowledge in the management of web-based library information systems. The development process included designing a training model, creating training modules, training materials, and web-based training media. The training combined practical and theoretical models, with simulations of the use of web-based library information systems. Evaluation was conducted through performance tests and validation by experts. The evaluation results showed that the training design was rated as excellent by the experts, with an average score of 86.70% for the material and 89.30% for the media. The final product is considered internally valid and can be implemented. The scores from the questionnaire test of the trainees showed the success of the training with a percentage of 76.11%. Statistical tests showed that participants' knowledge increased significantly after the training. The N-Gain Score value of 62.68% indicates that the training model is quite effective.